Timing of Orchiopexy in the United States: A Quality-of-Care Indicator - Yiee, Jenny H. (2012)
OBJECTIVE: To investigate whether orchiopexies are occurring later than recommended by American Academy of Pediatrics 1996 guidelines (around age one). Adherence to guidelines is poorly studied. METHODS: Main Cohort: 4,103 boys insured from birth (Innovus i3, insurance claims database) Complementary cohort: 17,010 insured and non-insured boys (Pediatric Health Information System, PHIS) Inclusion criteria: age ≤5 years at time of ICD-9-defined cryptorchidism diagnosis Primary outcome: timely surgery (orchiopexy by age 18 months) RESULTS: In Innovus, 87% of boys who underwent an orchiopexy had a timely orchiopexy. Of those who did not undergo surgery (n=2738), 90% had at least one subsequent well-care visit. Those who underwent timely surgery were referred to a surgeon at a younger age compared with those who underwent late surgery (4.1 months vs. 16.1 months, p<.00005). Predictors of timely surgery were number of well-care visits (OR 1.5, 95% CI 1.3–1.7), continuity of primary care (OR 1.9, 95% CI 1.3–2.7), and use of laparoscopy (OR 4.5, 95% CI 1.4–14.9). Family/internal medicine as referring provider was predictive of delayed surgery (OR 0.5, 95% CI 0.3–0.8). In PHIS, 61% of those with private insurance had timely surgery compared with 54% of those without private insurance (p< 0.0001). CONCLUSIONS: We found an unexpectedly high adherence to guidelines in our continuously insured since birth Innovus population. Primary care continuity and well-care visits were associated with timely surgery. Further studies can confirm these findings in non-privately insured patients with the ultimate goal of instituting quality improvement initiatives.